Gender Stratification A Structural Model for Examining Case Examples of Women in Less-Developed Countries - laurie wermuth and miriam ma'at-ka-re monges (frontiers/2002/vol. 23, no. 1, 2002)
Feminist social history and theory have produced an array of approaches for the purpose of deconstructing historical records and theoretical frameworks that previously took for granted the second-class status and cultural insignificance of women. However, tools for systematic comparative analysis have not been fully integrated into the study of women's place across societies and social classes. A structural theory of gender stratification based on the work of Rae Lesser Blumberg and Randall Collins offers tools for the systematic and comparative study of women across societies and periods of history. By "structural" model we mean one that examines the institutional relationships of women and men in the economy, politics, and the family. This structural/materialist approach has remained in the domain of a relatively small group of sociologists and anthropologists for reasons that are not entirely clear. Blumberg, Collins, and others have developed theoretical models for the comparative study of gender equality.1 Relatively greater female control over sexuality and fertility, the timing of marriage, and partner choice reflect more equality. Increasing gender equality is also indicated by women's ability to divorce abusive husbands, share household authority, and exert local political influence. As a complement to detailed ethnographic and historical studies, a structural model offers promising tools for examining the forces that affect women's social and economic positions in less-developed countries. Such analyses can also fortify social and economic policy recommendations. The first section of this paper explains the gender stratification model, and the second discusses case examples from Kerala (India), southern Africa, and Cambodia. In the conclusion we list several policy implications.